The environmental challenge for central European economies in transition - Klarer, Jürg; Moldan, Bedřich (John Wiley & Sons, 1997)
An analysis of the nature and scope of the environmental challenge in the main countries of Central and Eastern Europe, including Albania, Bulgaria, Hungary, Poland, the Czech Republic and Slovakia.